Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

Subtract the sum of -1260 and 1328 from the sum of 1326 and -1468.

seo-qna
Last updated date: 15th Jul 2024
Total views: 345.9k
Views today: 8.45k
Answer
VerifiedVerified
345.9k+ views
Hint: We know that the positive of a positive number is positive, positive of a negative number is negative, negative of a positive number is negative and the negative of a negative number is positive. Using this concept, we can solve our problem by simplifying it in parts.

Complete step-by-step solution:
We all know very well that
+ (+) = (+)
+ (-) = (-)
- (+) = (-)
- (-) = (+)
Let us now solve our problem partwise.
First, we will calculate ‘the sum of -1260 and 1328’. We know that sum represents addition.
Hence, we get that the sum of -1260 and 1328 = -1260 + 1328.
We can also write this as, the sum of -1260 and 1328 = 1328 + (-1260).
Using the above concept, we can write the sum of -1260 and 1328 = 1328 - 1260.
Thus, we have the sum of -1260 and 1328 = 68.
Now, we will calculate ‘the sum of 1326 and -1468’. We know that sum represents addition.
So, we have the sum of 1326 and -1468 = 1326 + (-1468).
Using the above concept, we can write the sum of 1326 and -1468 = 1326 - 1468.
Therefore, the sum of 1326 and -1468 = -142.
On substituting these values, our question becomes ‘subtract 68 from -142’.
So, we can write,
Required result = -142 - 68.
Thus, we get, required result = -210.
Hence, -210 is the required answer.

Note: We could have also solved this problem by directly writing the final equation, which can be written as {1326 + (-1468)} - {(-1260) + 1328}. And then, we could have written this as 1326 - 1468 + 1260 - 1328. Hence, we will get the answer.